2017
DOI: 10.1111/eff.12374
|View full text |Cite
|
Sign up to set email alerts
|

Beaver dams, streamflow complexity, and the distribution of a rare minnow, Lepidomeda copei

Abstract: Freshwater fishes are threatened globally, and often too little is known about threatened species to effectively guide their conservation. Habitat complexity is linked to fish species diversity and persistence, and degraded streams often lack habitat complexity. Beaver Castor spp., in turn, have been used to restore streams and increase habitat complexity. The northern leatherside chub Lepidomeda copei is a rare, smallbodied, drift-feeding minnow that has anecdotally been observed to use complex habitats assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Previous research in our study system (the Bridge Creek watershed) demonstrated that beaver-based restoration increased habitat complexity, density, and survival of juvenile steelhead (Bouwes et al 2016). More broadly, beaver activity and beaver dam analogues are being promoted as a potential restoration tool to remediate channel incision (Pollock et al 2014) and increase habitat complexity for the benefit of fish populations (Bouwes et al 2016;Dauwalter and Walrath 2017). Our research provides important new insights into the mechanisms that may lead to enhance population productivity.…”
Section: Discussionmentioning
confidence: 60%
“…Previous research in our study system (the Bridge Creek watershed) demonstrated that beaver-based restoration increased habitat complexity, density, and survival of juvenile steelhead (Bouwes et al 2016). More broadly, beaver activity and beaver dam analogues are being promoted as a potential restoration tool to remediate channel incision (Pollock et al 2014) and increase habitat complexity for the benefit of fish populations (Bouwes et al 2016;Dauwalter and Walrath 2017). Our research provides important new insights into the mechanisms that may lead to enhance population productivity.…”
Section: Discussionmentioning
confidence: 60%
“…In arid and semi-arid landscapes, beaver dams increase water storage in streams and in adjacent floodplains, maintain water within the river course, and promote riparian vegetation [41]. Active and abandoned dams are associated with elevated structural and thermal heterogeneity of instream habits [4246] and increased woody vegetation in riparian habitats [47]. Gibson and Olden [41] provide a thorough review of the response of hydrology, geomorphology, water quality, riparian vegetation, and wildlife to the habitat manipulations of beaver.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous species utilize the complex and dynamic pool, pond and wetland habitat created by such obstructions and some of those species are in steep population decline. In addition to coho salmon, other rare or endangered species that benefit from beaver ponds include the willow fly catcher and yellow-legged frog [59–63]. We suggest the need for a more nuanced approach to fluvial ecosystem management, an approach that recognizes that a dynamic tension exists between the need for habitat connectivity and habitat quality, between the need for fast-water habitat and slow-water habitat.…”
Section: Discussionmentioning
confidence: 99%